2015
DOI: 10.1016/j.procir.2015.04.076
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Application for Geometrical Tolerancing Concepts Understanding

Abstract: The general concept and main capabilities of the application Geometrical Tolerancing that has been consequently developed by the authors for a couple of years to effectively present and disseminate the ISO GPS system rules in industry and technical universities are presented. The application structure is shortly shown and discussed through a few screen shoots. The paper is focused on the approach used to present differences between requirements defined by the position tolerance of the two hole pattern without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Humienny [ 49 ] rightly stated that international standards in the field of product geometry specifications lag behind the development of knowledge and the scientific basis of design and new developments in metrology. On the models developed, he showed that the surface interpretation of maximum and minimum material requirements is justified, as two accuracy requirements (dimensional tolerance and geometric tolerance) are transformed into one combined requirement.…”
Section: Assessment Of Accuracy In Grinding Processesmentioning
confidence: 99%
“…Humienny [ 49 ] rightly stated that international standards in the field of product geometry specifications lag behind the development of knowledge and the scientific basis of design and new developments in metrology. On the models developed, he showed that the surface interpretation of maximum and minimum material requirements is justified, as two accuracy requirements (dimensional tolerance and geometric tolerance) are transformed into one combined requirement.…”
Section: Assessment Of Accuracy In Grinding Processesmentioning
confidence: 99%
“…E-learning can optimize blended learning designs and pure online math courses (Simonova & Poulova, 2017). They are learning content that students and teachers can download and learn before meeting face-to-face in the classroom (Humienny & Berta, 2015). Thus, discussions, simulations, or practices will use face-to-face meetings.…”
Section: |mentioning
confidence: 99%
“…Sposób określania dopuszczalnej postaci tej różnicy określa GPS. Opis specyfikacji jest zatem poniekąd umową pomiędzy konstruktorem, technologiem oraz metrologiem co do tolerancji wymiarów oraz jakości wykonania wyrobu [2]. W projektowaniu konstrukcji stosuje się szereg tolerancji wymiarowych, w tym tolerancje kształtu.…”
unclassified